Pragmatics and literature - Chapman, Siobhan, 1968-; Clark, Billy (Linguistic approaches to literature ;, 2019)
"Pragmatics and Literature is an important collection of new work by leading practitioners working at the interface between pragmatic theory and literary analysis. The individual studies collected here draw on a variety of theoretical approaches and are concerned with a range of literary genres. All have a shared focus on applying ideas from specific pragmatic frameworks to understanding the production, interpretation and evaluation of literary texts. A full-length introductory chapter highlights distinctions and contrasts between pragmatic theories, but also brings out complementarities, shared aims and assumptions, and ways in which different pragmatic theories can make different contributions to our understanding of literary texts. The book as a whole encourages a sense of coherence for the field and presents insights from various approaches for systematic comparison. Building on previous work by the editors, the contributors and others, it makes a significant contribution to the growing field of pragmatic literary stylistics"--